Riboflavin and folic acid prevent aflatoxin production - D.N. MEHTA and H.C. DUBE*, R.J. VERMA, P.J. RAVAL (Indian Phytopathology, 2002)
Mycelial growth and aflatoxin production by Aspergillus parasiticus were reduced by including riboflavin or folic acid in the liquid growth medium. The production of aflatoxins B1 and G1 was reduced more than the production of B2 and G2. Aflatoxin production was reduced more than mycelial growth by both chemicals.